Culture and Parenting: Psychological Adjustment among Chinese Canadian Adolescents - Yoo, Cynthia S. M.; Miller, Lynn D. (Canadian Journal of Counselling and Psychotherapy, 2011)
This study examined the relationships between adolescents’ cultural identification, perceptions of maternal and paternal parenting, and psychological adjustment with a sample of 192 Chinese Canadian adolescents. Participants were recruited from public urban high schools and completed 4 self-report questionnaires. Data were analyzed using correlation and regression analyses. Results revealed that neither demographic nor cultural variables were significantly associated with psychological adjustment. Perceived maternal/paternal warmth was significantly and positively correlated with psychological adjustment and partially mediated the effect of perceived maternal/paternal control on psychological adjustment. The implications of these findings for counselling practice and future research are discussed.